Akibat Hukum Malpraktik yang Dilakukan oleh Tenaga Medis - Julius Roland Lajar; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2020)
Malpractice refers to an act of negligence or an act with the correct standard operating procedures but causes harm to consumers, in this case the patients and this can threaten the health and safety of the patient. Malpractice committed by medical personnel is certainly very detrimental to those who need medical treatment and greatly affects the hospital’s integrity which is certainly the center for all medical actions. Based on this, this study examines what the legal regulatory for medical personnel who commit malpractice and how to sanction his speech are. To uncover the issues a normative research method is used by applying the legislative approach that examines the applicable laws and regulations and a conceptual approach to reviewing library materials in the form of theories and opinions of legal experts. The legal regulatory for malpractice actions by medical personnel are regulated in several laws and regulations providing basic guidelines regarding malpractice actions committed by medical personnel. The regulations are found in the medical and health laws which provide legal certainty for the injured. This is a characteristic of the law itself in upholding justice. Malpractice acts committed by health workers have been regulated in the legislation No. 23 of 1992 concerning Health and the Medical Code of Conduct in force. In addition there are sanctions for the actions of medical personnel commiting malpractice, including criminal sanctions, civil sanctions, administrative sanctions and moral sanctions.